(untitled) (American Journal of Islam and Society, 2001)
This paper seeks to present a critique of and an alternative to theories and theorizing employed by social scientists to explain the relationship between religion and politics in general and Islamic Political Experience in particular. Within the context of the paper we argued that politcal theory can be conveniently understood in terms of the co-existence of two distinct and rival styles of though Positivism and historicism. For the lack of better terms we take positivism and historicism to be conventional and radical paradigms respectively. The paradigms are found wanting in that they do not have the capacity to provide a satisfactory framework of ideas and common vocabularly with which to conduct discourse on Islamic Political Experience. In any case, for a paradigm to do that, it must become fully subsumed in an Islamic worldview. A paradigm presented as a critique and alternative to these paradigms is based on conceptual analysis, with pure Qur’anic and Shariah concepts providing both the framework and methdological tools of analysis. It is an axiomatic approach as it involves systematic analysis of a number of axioms, the starting point of which is the idea of the totality of Islam as an ideal which Muslims endeaovur to concretize.